Stepping Towards Better Health: The Effects of Walking Football for 12 Weeks on Cardiovascular Health in Hypertensive Male Senior Citizens - Haq, Mir Ahsan Ul; Tiwari, Sandhya; Tiwari, Sandeep (Physical Education Theory and Methodology, 2024)
Background. Cardiovascular concerns in hypertensive elderly men, evaluating the effectiveness of a walking football program for targeted health improvement in this population. Study purpose. This study aims to clarify and characterize changes in cardiovascular health due to a 12-week walking football training program in male seniors (60-70 years) with hypertension. Materials and methods. This study engaged 60 male participants aged 60 to 70 years from diverse regions of Kashmir, India with hypertension. Purposive sampling was used to select individuals who hadn’t participated in physical activities for six months. In addition, participants were split into two groups: experimental and control. The study’s design and objectives were explained to participants one week before testing. Baseline data was collected a week prior to the 12-week program. The experimental group attended thrice-weekly, 1-hour walking football sessions with 10-minute warm-up, a 45-minute game, and 5 minute cool-down. Assessments were conducted at the end of the 4th, 8th, and 12th weeks. To analyze the data, a 2 (group: experimental, and control) X 4 (time: baseline, 4th week, 8th week, and 12th week) mixed ANOVA was conducted. Results. During the study, the control group displayed a slight decrease in systolic blood pressure (SBP) by week 8, which returned to baseline levels by week 12. Conversely, the experimental group demonstrated a consistent decline in systolic (SBP) and diastolic blood pressure (DBP), as well as resting heart rate (RHR), with a significant decrease observed by week 12. Additionally, basal metabolic rate (BMR) steadily increased in the experimental group over the 12 weeks. On the other hand, the control group exhibited no significant changes in DBP, RHR, or BMR throughout the duration of the training program. Conclusions. Walking football proves beneficial for hypertension, highlighting its public health potential. Research advocates its integration into interventions for community well-being.